2014
DOI: 10.1162/jocn_a_00575
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expressions and the Evolution of the Speech Rhythm

Abstract: In primates, different vocalizations are produced, at least in part, by making different facial expressions. Not surprisingly, humans, apes, and monkeys all recognize the correspondence between vocalizations and the facial postures associated with them. However, one major dissimilarity between monkey vocalizations and human speech is that, in the latter, the acoustic output and associated movements of the mouth are both rhythmic (in the 3- to 8-Hz range) and tightly correlated, whereas monkey vocalizations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 105 publications
(147 reference statements)
7
60
0
Order By: Relevance
“…Interestingly, breaking down the evoked responses into band-passed local field potentials (LFPs) revealed that the theta frequency band in this rostral region carried the most information about vocalizations. This is consistent with the idea that the structure of monkey vocalizations (like the structure of speech) may exploit neural activity in the theta band [15,16]. …”
Section: Vocalization- and Voice-sensitivity In The Neocortexsupporting
confidence: 90%
“…Interestingly, breaking down the evoked responses into band-passed local field potentials (LFPs) revealed that the theta frequency band in this rostral region carried the most information about vocalizations. This is consistent with the idea that the structure of monkey vocalizations (like the structure of speech) may exploit neural activity in the theta band [15,16]. …”
Section: Vocalization- and Voice-sensitivity In The Neocortexsupporting
confidence: 90%
“…It is thought that the speech rhythm parses the signal into basic units from which information on a finer (faster) temporal scale can be extracted [46]. Given the importance of this rhythm in speech and its underlying neurophysiology [53, 54], understanding how speech evolved requires investigating the origins of its bi-sensory rhythmic structure.…”
Section: On the Origins Of The Speech Rhythmmentioning
confidence: 99%
“…We do know that macaque monkey vocalizations have a similar acoustic rhythmicity as human speech but without the concomitant and temporally-correlated rhythmic facial motion [55]. Modulation-spectra analyses of the acoustic rhythmicity of macaque monkey vocalizations reveal that their rhythmicity is strikingly similar to that of the acoustic envelope for speech [55] (Figure 2A). Both signals fall within the 3 – 8 Hz range (see also [56] for shared low-frequency components of macaque monkey calls and speech).…”
Section: On the Origins Of The Speech Rhythmmentioning
confidence: 99%
“…Thus, marmoset vocal communication, like human speech communication, can be modeled as loosely coupled oscillators. As a mechanistic description of vocal turn taking, coupled oscillators are advantageous since they are consistent with the data from speech processing that brain oscillations are critical to temporal structure [Giraud and Poeppel, 2012;Hasson et al, 2012] and its evolution [Ghazanfar and Takahashi, 2014]. Further, such oscillations do not necessarily require any higher-order cognitive capacities to operate [Takahashi et al, 2013].…”
Section: Cooperative Communication: Turn Taking In Humans and Marmosementioning
confidence: 63%